Spatiotemporal variations in the eco-health condition of China's long-term stable cultivated land using Google Earth Engine from 2001 to 2019. (December 2022) - Li, Guangyu; He, Tingting; Zhang, Maoxin; Wu, Cifang
Abstract: Long-term stable cultivated land (LSCL) is associated with food security. However, relevant studies about monitoring the eco-health condition (EHC) change of LSCL are insufficient at the national level. In our study, the Google Earth Engine platform and the remote sensing pixel-based ecological index model (RSEI-2) were employed to detect the EHC change tendency of LSCL from 2001 to 2019 at the national level. The results showed that approximately half of the LSCL EHC is increasing (56.57%) in China. The EHC increase was present in northeastern and southwestern of China. The EHC decrease occurred in northwestern China and the Inner Mongolia area, which have low rainfall. The results of drought division have proven that the limitation of rainfall could increase the risk of EHC degradation on the LSCL. The analysis of field size showed that large field size LSCL plots (16–25 ha) could increase the EHC (approximately 8-fold), while the very large field size LSCL plots (25–100 ha) showed little positive effects (approximately 1-fold). Population urbanization has played a negative role in the sustainability of LSCL. Low urbanization showed a significant positive effect on the EHC of LSCL. To protect LSCL, we propose optimizing farmers' cropping structure and management methods through the incentives and supervision of policy instruments. Highlights: A pixel-based model (RSEI-2) is applied on LSCL at the national level. The half of the LSCLs' EEQ is improving at the national level. The drought is threatening in EEQ of LSCL. The EEQ increasing presented in large field size LSCL (16–25 ha). Population urbanization cause EEQ decreasing of LSCL.